Influence of Visual Framing Code in Sundanese Golek Performance on Television - Irfansyah, Irfansyah (ASPENSI in Bandung, Indonesia, 2013)
ABSTRACT: The art of âwayang golekâ or âgolekâ is indigenous to Sundanese people. As a Sundanese traditional art, âgolekâ has been developed within generations of Sundanese people up to these days, based on a convention called âpakemâ or âtetekonâ. âGolekâ is a variety of âwayangâ (Indonesian shadow puppet) made of wood, similar to a doll and can be moved freely. âWayang golekâ is usually performed in an open space, throughout the night. Sundanese people commonly hold a âgolekâ performance for a ritual such as âruwatanâ and âsekatenanâ that commemorates âMaulid Nabi Muhammad SAWâ. However, since time has passed, marked by the existence of mass media in the form of television (TV) among Sundanese people, âgolekâ performance started to be broadcasted on TV. Since the performance of âgolekâ on TV has been possible, it represents a significant difference compared to traditional âgolekâ performance, which is marked by the visual language of television or âvisual framingâ, such as zoom in/out, panning, tilt up/down, close up, medium close, etc. The change in visual representation of âgolekâ on TV becomes sensational and entertaining, compared to traditional âgolekâ performances which are symbolic and ritual. KEY WORDS: Change, code, visual framing, âwayang golekâ, Sundanese society, television, and entertainment.About the Author: Irfansyah is a Leturer at the Study Program of Visual Communication Design, Faculty of Fine Art and Design ITB (Bandung Institute of Technology), Jalan Ganesha No.10 Tamansari, Bandung 40132, West Java, Indonesia. E-mail address: fandkv@yahoo.co.idHow to cite this article? Irfansyah. (2013). âInfluence of Visual Framing Code in Sundanese Golek Performance on Televisionâ in TAWARIKH: International Journal for Historical Studies, Vol.4(2) April, pp.245-262. Bandung, Indonesia: ASPENSI [Asosiasi Sarjana Pendidikan Sejarah Indonesia] and UVRI [Universitas Veteran Republik Indonesia], ISSN 2085-0980. Chronicle of the article: Accepted (February 10, 2013); Revised (March 14, 2013); and Published (April 28, 2013).